Diabetes rescue, engagement, and management (D-REM) for hypoglycemia: Clinical trial protocol of a community paramedic program to improve diabetes management among adults with severe hypoglycemia - Sumit Bhagra; Allison L. Ducharme-Smith; Michael B. Juntunen; Chad P. Liedl; Elizabeth H. Golembiewski; Wendy J. Sundt; Tami S. Krpata; Michelle A. Lampman; Anna L. Espinoza; Rozalina R. McCoy (PLoS ONE, 2025)
Background Diabetes is among the most prevalent chronic conditions in the United States. Challenges in optimal diabetes care include fragmented care, gaps in diabetes self-management education, and high treatment burden. Severe hypoglycemia, a serious and potentially preventable event, indicates the need for treatment optimization. Inadequate or inaccessible care increases hypoglycemia risk. Community paramedics are well-positioned to fill these care gaps by providing focused diabetes self-management education and improving patient self-efficacy. Integrating community paramedics into care teams offers a novel pathway to improve diabetes outcomes. Methods and analysis We will conduct a pragmatic 2-group, parallel-arm, randomized clinical trial of a community paramedic–led “Diabetes Rescue, Engagement, and Management” program to enhance diabetes self-management in patients with a history of hypoglycemia. The study will enroll 150 adults (≥18 years) with diabetes and a history of level 3 hypoglycemia from 5 counties in Minnesota. Participants identified as having hypoglycemia (from an integrated health system and the primary ambulance service in the area) will be randomly assigned to the program intervention or to usual care. The intervention group will receive community paramedic home visits for approximately 1 month to deliver diabetes self-management education tailored to individual needs. Both groups will receive written diabetes education and resource materials. Outcomes include change in diabetes self-management, hypoglycemia, hyperglycemia, hemoglobin A1c level, diabetes distress, and health-related quality of life, assessed at baseline, 1 month, and 4 months. Qualitative interviews of 16 intervention participants and 16 persons who decline participation will be analyzed to understand the program’s effects and reasons for nonparticipation, to inform future program design. Trial registration ClinicalTrials.gov NCT04874532